Parasitic Patch of the Same Dimensions Enabled Excellent Performance of Microstrip Antenna Array - Tang, Mingchun; Xiao, Shaoqiu; Deng, Tianwei; Wang, Duo; Wang, Bingzhong (Applied Computational Electromagnetics Society Journal (ACES), 2022)
This paper presents a thorough investigation on the use of parasitic patch as an effective secondary radiator to suppress mutual coupling and improve the gain of a microstrip array. The measured results show that the proposed parasitic patch placed halfway between elements in the E-plane of two-element array not only suppresses mutual coupling by 7.3dB, but, also, improves the gain by 1.6dB. By further simulation and comparison, the results indicate the proposed parasitic patch is quite suitable for application into the high-density microstrip arrays.